Discovery of Kilohertz Quasi-periodic Oscillations in 4U 1735-44 - Wijnands, Rudy (1998)
We discovered a single kilohertz (kHz) quasi-periodic oscillation (QPO) near 1150 Hz in the Rossi X-Ray Timing Explorer X-ray light curve of the low-mass X-ray binary and atoll source 4U 1735-44. The rms amplitude of this peak was 2%-3%, and the FWHM was 6-40 Hz. There are indications that the kHz QPO frequency decreased from 1160 to 1145 Hz when the count rate increased, which would be quite different from what is observed in other atoll sources for which kHz QPOs have been discovered. In the X-ray color-color diagram and hardness-intensity diagram, the source traced out the curved branch (the so-called banana branch) that has been found by previous instruments. The kHz QPO was detected only when the source was at the lowest count rates during our observations, i.e., on the lower part of the banana branch. When 4U 1735-44 was at higher count rates, i.e., on the upper part of the banana branch and at a higher inferred mass accretion rate with respect to that on the lower part of the banana branch, the QPO was not detected. Besides the kHz QPO, we discovered a low-frequency QPO with a frequency near 67 Hz, together with a complex, broad-peaked noise component below 30 Hz. This 67 Hz QPO may be related to the magnetospheric beat-frequency QPO, which is observed on the horizontal branch of Z sources. This idea is supported by the (peaked) noise found in both 4U 1735-44 and Z sources at frequencies just below the QPO frequency.